Introduction to genetic analysis (Macmillan, 2020)
"The twelfth edition of Introduction to Genetic Analysis takes this cornerstone textbook to the next level. The hallmark focus on genetic analysis, quantitative problem solving, and experimentation continues in this new edition. New to the twelfth edition are Chapter Objectives and Core Principles. Each chapter begins with a two-sentence paragraph describing the goals of the chapter and placing the chapter topic into context of the surrounding chapter. This helps students "see the forest" before stepping into the "trees". Introduction to Genetic Analysis divides genetics into three segments : transmission genetics, molecular genetics, and evolutionary genetics. Each part of the text now begins with a three- to five-page introduction outlining the core principles that characterize that segment of genetics. These help orient students by providing an overview of the themes they'll encounter as they read each part."--